Synthesis and Characterization of New Oxazepines Compounds Derived From D- Galactose (Journal of the College of Basic Education, 2022)
New Schiff bases derived from D-galactose were synthesized by condensation of aldehyde (1,2:3,4-Di-O-isopropylidene-6-carboxaldehyde-α-D-galactopyranose) with different aromatic amines such as (4-bromo, 3-hydroxy, 4-iodo, 4-methoxy) aniline in dry benzene using glacial acetic acid as a catalyst. These compounds were converted to oxazepine derivatives by additionreaction with maleic anhydride in dry benzene as a solvent. The structures of the synthesized compounds have been characterized by elemental analysis, FTIR spectra, some of them by using 1HNMR spectra and measurement of its physical properties.